2022
DOI: 10.1108/jkm-10-2021-0753
|View full text |Cite
|
Sign up to set email alerts
|

The power of knowledge management: how top management team bricolage boosts ambidexterity and performance

Abstract: Purpose This paper aims to explore the relationship between top management team bricolage and performance and also examines unit ambidexterity's mediating role. More essentially, to understand the black box of organizational knowledge dynamism, a multilevel moderated mediating model is established by exploring the effects of two firm-level moderators, namely, potential absorptive capacity and realized absorptive capacity. Design/methodology/approach To test the cross-level moderated mediation model, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…The top leader's ability to balance dual modes of learning, balancing dualities and paradoxes of change and stability, control and flexibility and local and global pressures by adopting an ambidextrous leadership style (Probst et al, 2011;Heavey et al, 2015;Zacher and Rosing, 2015) has been noted as a critical approach in creating an ambidextrous context (Chang et al, 2022;Cunha et al, 2019;Malik et al, 2017Malik et al, , 2019. In a resourceconstrained and emerging market context, an ambidextrous leadership style is critical in balancing the tensions that dualities present and achieving OA.…”
Section: Ambidextrous Leadership In Small-and Medium-enterprisesmentioning
confidence: 99%
“…The top leader's ability to balance dual modes of learning, balancing dualities and paradoxes of change and stability, control and flexibility and local and global pressures by adopting an ambidextrous leadership style (Probst et al, 2011;Heavey et al, 2015;Zacher and Rosing, 2015) has been noted as a critical approach in creating an ambidextrous context (Chang et al, 2022;Cunha et al, 2019;Malik et al, 2017Malik et al, , 2019. In a resourceconstrained and emerging market context, an ambidextrous leadership style is critical in balancing the tensions that dualities present and achieving OA.…”
Section: Ambidextrous Leadership In Small-and Medium-enterprisesmentioning
confidence: 99%
“…For example, Gibson and Birkinshaw (2004) assessed 4,195 managers and nonmanagers within 41 different business units during a three-year period and concluded that business units that exhibited ambidextrous behavior performed better than those that did not. Additionally, according to Chang et al (2022), ambidexterity plays a mediating role between top management’s diversity and organizational units’ performance. Exploration and exploitation activities are also crucial prerequisites for performance of family firms (Hughes et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be done by successfully adopting and applying innovation and current market knowledge (Chiu and Chen, 2016;AlMulhim, 2021a). At present day, Knowledge management capability and performance knowledge has become an important reserve and source for strengthening organizational performance (Manfredi Latilla et al, 2018;Chang et al, 2022). According to Grant (2015), organizations prerequisite to be prepared with improved resources and capabilities than their rivals to reservation of their competitive benefits in the vibrant market system.…”
Section: The Relationship Between Knowledge Management Capability (Km...mentioning
confidence: 99%